2022
DOI: 10.1099/mgen.0.000760
|View full text |Cite
|
Sign up to set email alerts
|

The virulome of Streptomyces scabiei in response to cello-oligosaccharide elicitors

Abstract: The development of spots or lesions symptomatic of common scab on root and tuber crops is caused by few pathogenic Streptomyces with Streptomyces scabiei 87–22 as the model species. Thaxtomin phytotoxins are the primary virulence determinants, mainly acting by impairing cellulose synthesis, and their production in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…This is most likely a consequence of the activation of concanamycin antioomycete compounds as cellobiose, along with cellotriose, is a potent elicitor of the virulome of S . scabiei 28,4245 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most likely a consequence of the activation of concanamycin antioomycete compounds as cellobiose, along with cellotriose, is a potent elicitor of the virulome of S . scabiei 28,4245 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, earlier work reported antioomycete activities for strain PK-A41 of S . scabiei 26 , and genomic and metabolomic studies confirmed its capability to produce concanamycin derivatives active against bacteria, fungi, and oomycetes 27,28 . How will S .…”
Section: Introductionmentioning
confidence: 86%
“…The analysis indicates that the WPN32 strain has the potential for synthesising various antimicrobial agents, including albaflavenone [1] , ε-Poly-L-lysine [2] , informatipeptin [3] , and setomimycin [4] ( Table 2 ).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Interestingly, cellobiose and cellotriose were found to possess a function other than providing energy in S. scabiei strains. As a major molecule released in the expansion period of plant tissues, cellotriose is proposed as the best inducer and trigger of the synthesis of virulome, including thaxtomin [ 16 , 17 ]. It has been authenticated that the cello-oligosaccharide transport system CebEFG-MsiK is essential for the induction of thaxtomin in pathogenic Streptomyces strains [ 4 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%